Strategi Kolaboratif Akreditasi dan Total Quality Management dalam Transformasi Mutu Pendidikan di Pesantren - Ulfa Qomariatul Jannah; Misbahul Arifin (Education Research Center, 2025)
This study aims to examine the integration of accreditation and Total Quality Management (TQM) in improving educational quality in Islamic boarding schools (pesantren). Using a qualitative approach with a case study at the Muadalah Education Unit of Al-Mashduqiah Islamic Boarding School, data were collected through observation, in-depth interviews, and documentation studies with three groups of informants: room guardians, boarding school administrators, and student guardians. The results indicate that understanding and implementation of the collaborative strategy of accreditation and TQM are not evenly distributed among stakeholders, with the dominant role of boarding school administrators and minimal participation from both student and student guardians. The implementation of TQM principles, such as the PDCA cycle and the involvement of all educational elements, remains suboptimal. Although there has been an increase in learning outcomes among active students, the quality strategy has not yet become a comprehensive culture. This study concludes that the integration of accreditation and TQM can drive systemic transformation of educational quality if implemented in a participatory and sustainable manner